Introduction of vegetables for crop diversification among cereal growers in Indo-Gangetic Plains - Burman, Rajarshi Roy; Singh, Rahul; Sharma, Shailendra; Rao, D U M; Singh, V K; Singh, A K (Indian Farming, 2021)
Vegetable cultivation introduced as an experiment in farmers’ fields on trial basis in 500 sq mplot has provided adequate evidence to show the remunerative potential of vegetable cultivationand a strong motivating force to attract and retain young farmers in agriculture. In the threeICAR-Farmer FIRST Programme (FFP) villages of Palwal district of Haryana, vegetablegrowers grew from 465 farmers in 2017-18 to 655 in 2018-19 and 797 in 2019-20, showing anincreasing trend in growing number of farmers interested in vegetable cultivation. Acreage undervegetables in rice-wheat cropping Indo-Gangetic plains of three ICAR-FFP villages rose from57.44 acres in 2017-18 to 89.02 acres in 2018-19 and 115.08 acres in 2019-20. Vegetablecultivation has proved to be a great catalyst in bringing about transformation in the villages asmany resource-poor small and marginal farmers have started weaning away from cereal cropproduction and moving towards vegetable cultivation. This change in diversification will go along way in changing the outlook of young farmers to continue to perceive farming as aremunerative profession. This will restore faith of farmers in remunerative potential of vegetablefarming.